FAO conservation guide N.24 - Edgar Hernandez Becerra (FAO, 1995)
This paper comprises two parts: " a technical guide " and " the story of Engineer Funes ", the manager of a typical watershed management project. At the end of each technical section, we describe how Funes and his assistants put into practices the suggestions contained in the technical part. The focal point of the technical guide is Chapter 4, which dal with the design of a watershed management monitoring system.